Risk of stroke associated with proton pump inhibitor use among individuals with and without pre-existing cardiovascular diseases: a systematic review and meta-analysis - Muhammed Shabil; Bijaya K. Padhi; Mahalaqua Nazli Khatib; Soumya V. Menon; Mandeep Kaur; Mukesh Kumari; Puneet Sudan; K. Satyam Naidu; Quazi Syed Zahiruddin; Sarvesh Rustagi; Divya Sharma; Mithhil Arora; et al. (Journal of Cardiothoracic Surgery)
Abstract Background Proton pump inhibitors (PPIs) are commonly used for managing gastroesophageal disorders but concerns about their potential association with increased stroke risk have emerged, especially among patients with pre-existing cardiovascular conditions such as acute coronary syndrome (ACS). This systematic review and meta-analysis aim to assess the risk of stroke associated with PPI use, stratified by the presence or absence of pre-existing CVD. Methods This review was conducted following the PRISMA guidelines and included studies up to March 2024 from PubMed, Embase, and Web of Science. Eligible studies were longitudinal, including prospective cohorts, nested case-controls, and post-hoc analyses of RCTs that reported stroke outcomes in relation to PPI use. Data were synthesized using random-effects meta-analysis models in R software version 4.3. Results Our search yielded 41 studies encompassing over 800,000 participants globally. Meta-analysis of 14 observational studies revealed a slight but non-significant increased stroke risk among patients with prior CVD (pooled HR = 1.222, 95% CI: 0.963 to 1.481, I² = 78%). In contrast, analysis of 15 studies without prior CVD showed a modestly increased risk (pooled HR = 1.15, 95% CI: 1.023 to 1.288, I² = 98%). Five RCTs involving patients with CVD reported a pooled RR of 1.158 (95% CI: 0.914 to 1.466), indicating no significant risk increase. Conclusion The association between PPI use and stroke risk appears modest and is influenced by the presence of cardiovascular conditions. Clinical decision-making should consider individual patient risk profiles, and further high-quality studies are needed to guide safer PPI prescribing practices.